Falloff curves and mechanism of thermal decomposition of CF₃I in shock waves - Cobos, Carlos Jorge (2019)
The falloff curves of the unimolecular dissociation CF₃I (+Ar) → CF₃ + I (+Ar) are modelled by combining quantum-chemical characterizations of the potential energy surface for the reaction, standard unimolecular rate theory, and experimental information on the average energy transferred per collision between excited CF₃I and Ar. The (essentially) parameter-free theoretical modelling gives results in satisfactory agreement with data deduced from earlier shock wave experiments employing a variety of reactant concentrations (between a few ppm and a few percent in the bath gas Ar). New experiments recording absorption-time signals of CF₃I, I₂, CF₂ and (possibly) IF at 450-500 and 200-300 nm are reported. By analysing the decomposition mechanism, besides the unimolecular dissociation of CF₃I, these provide insight into the influence of secondary reactions on the experimental observations.